Implementasi Strategi Marketing Public Relation dalam Meningkatkan Loyalitas Nasabah dan Citra Perusahaan - Izzaini, Muhammad Fadhil (Maliki Interdisciplinary Journal, 2024)
This article discusses the implementation of Marketing Public Relations (MPR) strategies and their impact on companies, especially in increasing customer loyalty and corporate image in the banking and insurance sectors. In the current era of globalization, which is indicated by intense competition in every field, companies are not only required to offer quality products, but also build strong relationships with customers. In building these strong relationships, MPR plays a role as an effective communication bridge between a company and the public, helping to shape positive customer perceptions and increase their trust. Through activities such as events, sponsorships, and social media campaigns, companies can create positive experiences that encourage customer loyalty. This research shows that transparent and interactive communication not only increases customer satisfaction but also contributes to a company’s reputation. As such, MPR is an essential strategy in customer relationship management, and it enables companies to respond quickly to issues and maintain a positive image in the eyes of the public. This article aims to provide some insight into the importance of MPR and its implementation, its impact on customer loyalty and corporate image in the context of modern business and the challenges faced by companies and their solutions.